Overview of Self-Management in Hypertension Patients in the Working Area of Sidomulyo Samarinda Health Centre - Fanny Metungku; Mayusef Sukmana; Khumaidi; Nanda Muliadi (Fakultas Kedokteran, Universitas Mulawarman, 2023)
Background: Hypertension or high blood pressure that many people know can cause death without complaints and is so dangerous that it gets the nickname